ANALISIS TINDAK TUTUR ILOKUSI PADA FILM "KELUARGA CEMARA" (2019) KARYA YANDY LAURENS DAN KEDUDUKANNYA DALAM KURIKULUM 2013 - Bella, Bella Fauzi Auliska; Dheni Harmaen; Marlia (Journal of Education for The Language and Literature of Indonesia, 2023)
This study purpose to description results of illocutionary speech acts from film “Keluarga Cemara” (2019) Yandy Laurens and position in curriculum 2013. This research was conducted on the basis of a lack of understanding when listening to information, so that misunderstandings often occur. This is accompanied by the opinion of Tarigan (2021, p. 109) who says that the influencing factor of listening is the experience factor. Background experience is an important factor in listening activities. A lot of vocabulary understanding when listening also affects listening skills. Therefore, research on illocutionary speech acts was carried out in the film “Keluarga Cemara”. This study illocutionary speech acts refer by theory Searle (1969). This research is research qualitative. Method this research use method observe and method note. Data source this research use primer data source, the data is film “Keluarga Cemara” (2019) by Yandy Laurens. The results of this study are: first, the resuts of analysis illocutionary speech acts film “Keluarga Cemara” (2019) by Yandy laurens to found out 95 data of illocutionary speech acts. The data to found out by researcher is 40 data of illocutionary assertive, 32 data of illocutionary directive, 17 data of illocutionary expressiveness and 6 data of illocutionary commissiveness. Second, the results analysis illocutionary speech acts film “Keluarga Cemara” (2019) can used as teaching materials or media learning for Indonesian language subject at the junior high school. The subject matter is review text and can found in KD 4.11. KD (Basic Kompetencies) is found at Junior High School and the level subject matter in class VIII.